STUDI KELAYAKAN PEMASANGAN OPTIMAL STATIC VAR COMPENSATOR PADA PENYULANG SUATU SISTEM KELISTRIKAN INDUSTRI - , PRATAMA DONNIE FADHLILLAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Abstractâ To overcome the forecasted industrial system expansion in 2017, the company has prepared several options of solutions. This research reviews the feasibility of one option, which is by unifying load power factor using static var compensator. The SVC bus placement and size are optimized by using the proposed optimization program based on genetic algorithm method. Three objectives are introduced to be satisfied by the proposed program. The feasibility of the recommended SVC are determined in technical perspective, i.e. power loss and voltage magnitude, and economic perspective, i.e. investment cost and annual saving. Comparison to other option of compensator device, capacitor bank, is also presented in both perspectives.